Technical strategies and pitfalls for total transfemoral implantation of off-the-shelf four vessel thoracoabdominal multibranch endoprosthesis with or without utilization of preloaded wires - Sukgu M. Han, MD, MS; Alyssa Pyun, MD; Gustavo S. Oderich, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
The thoracoabdominal multibranch endoprosthesis is a commercially available off-the-shelf four-vessel inner branched endograft for complex abdominal and thoracoabdominal aortic aneurysms. Although the device is intended to be used with upper extremity access per its instructions for use, total transfemoral approach may be needed in patients with unfavorable arch anatomy and may decrease the risk of cerebrovascular events. This article describes technical strategies and pitfalls of total transfemoral thoracoabdominal multibranch endoprosthesis implantation techniques with conventional co-axial steerable sheath, as well as variations of techniques utilizing preloaded wires in “up-and-over” configuration.